Surgical techniques of the shoulder, elbow, and knee in sports medicine - Cole, Brian J.; Sekiya, Jon K. (Elsevier/Saunders, 2013)
Presents you with a step-by-step approach on performing both open and arthroscopic surgeries for sports-related injuries. This book offers all of the expert guidance you need on everything from patient positioning and the latest orthopaedic surgery techniques, through pearls and pitfalls and post-operative care.